2009
DOI: 10.1016/s0027-9684(15)30981-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Variation in Serum IGFI and IGFBP3 Levels in Healthy African American and White Men

Abstract: Background Individual variation in circulating insulin-like growth factor-I (IGF1) and its major binding protein, insulin-like growth factor binding protein-3 (IGFBP3) have been etiologically linked to several chronic diseases, including some cancers. Factors associated with variation in circulating levels of these peptide hormones remain unclear. Methods Multiple linear regression models were used to determine the extent to which socio-demographic characteristics, lifestyle factors, personal and family hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…While some studies reported correlation with reduced IGF-I levels [23, 25], others found that the IGF-I (CA) 19 repeat did not predict plasma levels [27, 65]. However, these findings are consistent with those of our previous reports where the effects of the IGF-I (CA) 19 polymorphism on circulating concentrations of IGF-I varied considerably by race/ethnicity [66], and associated with prostate cancer risk [67]. A recent study in a Chinese population, further analyzed the potential causes of these ethnic differences and found that the IGF-I (CA) 19 repeat by itself is not the primary regulatory element of IGF-I expression [68].…”
Section: Discussionsupporting
confidence: 88%
“…While some studies reported correlation with reduced IGF-I levels [23, 25], others found that the IGF-I (CA) 19 repeat did not predict plasma levels [27, 65]. However, these findings are consistent with those of our previous reports where the effects of the IGF-I (CA) 19 polymorphism on circulating concentrations of IGF-I varied considerably by race/ethnicity [66], and associated with prostate cancer risk [67]. A recent study in a Chinese population, further analyzed the potential causes of these ethnic differences and found that the IGF-I (CA) 19 repeat by itself is not the primary regulatory element of IGF-I expression [68].…”
Section: Discussionsupporting
confidence: 88%
“…Previous literature shows considerable inter-individual variation of IGF-1 4, 13, 14 and a relatively low intra-individual variation 15, 16 indicating that IGF-1 levels represent a relatively stable individual physiological characteristic. Therefore, sharp increases in IGF-1 in the aging population (against age-related decrease) may surface as a reflection of more complex underlying disturbances in GH/IGF-1 homeostasis.…”
Section: Discussionmentioning
confidence: 91%
“…For example, factors such as obesity have been thought to cause variations in IGFBP-3. 78 This could be true considering the fact that we demonstrated this population to have an increased body mass index. 79 Also, IGFBP-3 could be working along with other factors associated with persistence of cervical lesions.…”
mentioning
confidence: 67%